CTHRC1 promotes wound repair by increasing M2 macrophages via regulating the TGF-β and notch pathways - Shu Qin; Jianghong Zheng; Zihuan Xia; Jin Qian; Chen-Liang Deng; Songlin Yang (2019)
The healing of acute wounds is vital to humans and is a well-orchestrated process that involves systemic and local factors. However, there is a lack of effective and safe clinical therapies. The collagen triple helix repeat containing 1 (CTHRC1) protein is a type of exocrine protein that has been recently reported to contribute to tissue repair. Our aim is to validate the promoting effects of CTHRC1 on the healing of acute wounds and to elucidate the underlying molecular mechanism. Therefore, we first established acute wound healing mouse models and confirmed that CTHRC1 accelerates the healing process of acute wounds. Then, we characterized wound macrophages using a polyvinylalcohol (PVA) sponge model and used Western blotting to investigate the molecular mechanism. We found that CTHRC1 increased the M2 macrophage population and the TGF-β expression level as a result of the activation of the TGF-β and Notch pathways, which eventually contributed to the promotion of wound healing. Inhibition of the Notch pathway showed attenuated M2 macrophage recruitment, and it decreased the TGF-β expression level. These results substantiate our hypothesis that CTHRC1 promotes wound healing by recruiting M2 macrophages and regulating the TGF-β and Notch pathways.